COVID-19 and the Pediatric Heart - Henriques, Cláudio (2022)
Coronavirus disease stormed into our lives in 2019 with first reports of infection occurring in Wuhan, China. It spares no one, despite having a traditionally milder course in children. Still, a novel hyperinflammatory post COVID-19 entity has emerged between the pediatric age group implicating higher severeness and cardiac disease. Multisystem inflammatory syndrome in children (MIS-C) shares several key characteristics with other hyperinflammation associated diseases and treatment options usually overlap between them. Immunomodulatory therapy has shown to reduce the risk of complications and severe disease. Vaccination can rarely be associated with severe side effects, but risk-benefit assessment has a favourable balance towards vaccination. Despite the scarcity of data, pediatric long COVID-19 symptoms have been systematically described with a significant impact on children’s lives in the long run.